Serological investigation of Aujeszky’s disease between 2019 and 2021 in Peninsular Malaysia - Li, Hong Xia; Wai, Michelle Cheng Fong; Abdul Rahaman, Nor Yasmin; Low, Suet Ee; Lee, Jia Xin; Cheah, Eric Heng Chow; Kam, Kok Yen; Yong, Raquel Li Hui; Ooi, Peck Toung (Universiti Putra Malaysia, 2024)
Aujeszky’s disease (AD) is a common disease that has spread worldwide. Various porcine viral diseases exist in Malaysia, where AD is the most common viral endemic disease in the country. The serological status of AD in Peninsular Malaysia was reported prior to 2018, but information after that date is very limited. Hence, our study investigated AD’s serological status in Peninsular Malaysia pig farms based on commercial samples submitted to the Faculty of Veterinary Medicine, Universiti Putra Malaysia, between 2019 and 2021. In this study, 2,780 serum samples were taken from 61 farms, and an enzyme-linked immunosorbent assay (ELISA) test was performed using the IDEXX Pseudorabies Virus gpl Antibody Test Kit for AD serology diagnosis. The results showed that the overall seropositive rate of Aujeszky disease virus (ADV) was 1.51% (42/2,780), which dropped from 2.62% (23/879) in 2019 to 0.53% (5/937) in 2020 and 1.45% (14/964) in 2021. In addition, 18.03% (11/61) of the 61 farms that submitted samples were infected with AD. The results indicate that AD still exists in Peninsular Malaysia, and some farms are at risk from the disease. Further analysis suggested that the quarterly seroprevalence of ADV may also be related to region. This study provides serological data on AD in Peninsular Malaysia, which helps to understand the prevalence and serological status of the disease. © Universiti Putra Malaysia Press.